Does European Cohesion Policy affect Regional Business Dynamics? - Paolo Veneri; Marcos Diaz Ramirez; Lukas Kleine-Rueschkamp (Investigaciones Regionales - Journal of Regional Research)
This paper assesses whether European Cohesion Policy funds from the 2007‑2013 programming period affected business dynamics in European regions. Using a regression discontinuity approach, the analysis shows that regions receiving more funds experienced higher firm births, without statistically significant firm deaths, resulting in positive net firm creation and growing firm-related employment. In addition, this study confirms previous findings in the literature according to which regions receiving more funds show higher increases gross value added per worker. Finally, funds have a significantly higher effect on net business employment creation in regions with lower levels of perceived corruption, although this is not necessarily conductive to higher levels of labour productivity in those regions.